The Development of Blended Learning Model using Edmodo to Train Student Critical Thinking Skills on Impulse-Momentum Topic - Yus Rama Denny; Indri Sari Utami; Siti Rohanah; Dewi Muliyati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
This study determines the effect of developing blended learning models using Edmodo on students’ critical thinking skills on impulse and momentum. The research method used in this study is ADDIE. The population in this study is class X MIA SMAN 4 Serang City. The sample of this study amounted to 31 students from class X MIA 2 as an experimental class using a blended learning model and 30 students from class X MIA 3 as a control class using a cooperative model. The test used in this study was seven indicators of critical thinking skills. These results indicate an increase in students’ critical thinking skills after being given treatment that is by using a blended learning model. The N-Gain value evidences a large increase in the experimental class that is 0.60 in the medium category and 0.23 in the low category in the control class. The average value of pretest and posttest is 5.27 and 9.77 in the control class, while in the experimental class is 5.65 and 16.61. These results show that there is an influence on the development of blended learning models for critical thinking skills on the momentum and impulses.